Assessing Fiscal Space : An Initial Consistent Set of Considerations. (Policy Papers; Policy Paper, 2016)
Fiscal space is a multi-dimensional concept reflecting whether a government can raise spending or lower taxes without endangering market access and debt sustainability. Making such a determination requires a comprehensive approach considering, among other things, initial economic and structural conditions, market access, the level and trajectory of public debt, present and future financing needs, and dynamic analysis of the liquidity and solvency of the fiscal position under alternative policies. Balancing these considerations involves careful analysis and judgment. Fund staff has over the years developed a variety of indicators to inform assessments of fiscal space in bilateral and multilateral surveillance. The Fund's core operational framework for such analysis is the debt sustainability framework, which includes a number of indicators, while allowing room for staff judgment. Surveillance also relies importantly on indicators developed by the Fiscal Affairs Department (FAD)--including those that have been used in the internal Vulnerability Exercise and Fiscal Monitors--while more recent methods based on fiscal stress tests and probabilistic approaches proposed in IMF (2016) are also promising. In addition, teams have used scenario analysis and general equilibrium modeling approaches to evaluate fiscal policy choices and their implications for sustainability. When applied to fiscal space, each indicator and approach has pros and cons and none covers all the relevant factors. Ultimately, therefore, assessing fiscal space requires judgment, informed by a broad range of tools. This note seeks to bring together various approaches developed by Fund staff to outline a consistent set of considerations and indicators to help inform assessments of fiscal space, especially for advanced and emerging markets. The intent is to facilitate continued consistency between country team assessments by providing some common considerations and approaches to inform their judgment. The proposed framework will support Fund surveillance and policy advice going forward, informing discussions of the appropriate fiscal stance at all stages of the economic cycle.